The challenges and opportunities of developing educational tours to Finland targeting the Chinese market - Li, Wei (2021)
The aim of this study was to investigate the challenges and opportunities of developing educational tours to Finland targeting the Chinese market. During the first decade of this millennium, the amount of educational tour groups to Finland from China has risen significantly. However, it is surprising to see materializing educational tours to Finland targeting the Chinese market has been challenging. Therefore, by conducting semi-structured qualitative interviews with professionals who have developed, operated or marketed educational tours to Finland, opportunities, challenges and development suggestions were aimed to be explored. The purpose of the study is answered through the following research questions: What are the challenges of developing educational tours to Finland targeting the Chinese market? What are the opportunities of developing educational tours to Finland targeting the Chinese market? What are the development suggestions for educational tours to Finland targeting the Chinese market? In order to research on this subject, 9 professionals were interviewed. During the data analyses, a qualitative thematic analysis method was used. The interviewees found the challenges to be the awareness of Finland as an educational tour destination, resistance from Finnish schools, capacity, pricing and post COVID-19 concerns. The interviewees found the opportunities to be the high reputation of Finnish education, digital experience and Arctic theme. The findings may help regional development agencies, service providers and tour operators to reflect and evaluate how they can take actions to improve the services and formulate development strategies towards the Chinese market. The main limitation of this study is the limited sample from China which does not warrant generalization of the result. As a recommendation, further research should be conducted by gathering samples from more professionals in the target market, identifying further what is the market needs, and especially examining the impact of China’s “Double Reduction” policy and recovery of educational tourism in the post COVID-19 era.